Ternary Pt-Ru-Ni catalytic layers for methanol electrooxidation prepared by electrodeposition and galvanic replacement - Papaderakis, Athanasios; Pliatsikas, Nikolaos; Prochaska, Chara; Papazisi, Kalliopi M.; Balomenou, Stella P.; Tsiplakides, Dimitrios; Patsalas, Panagiotis; Sotiropoulos, Sotiris (Frontiers in Chemistry, 2014)
Ternary Pt-Ru-Ni deposits on glassy carbon substrates, Pt-Ru(Ni)/GC, have been formed by initial electrodeposition of Ni layers onto glassy carbon electrodes, followed by their partial exchange for Pt and Ru, upon their immersion into equimolar solutions containing complex ions of the precious metals. The overall morphology and composition of the deposits has been studied by SEM microscopy and EDS spectroscopy. Continuous but nodular films have been confirmed, with a Pt ÷ Ru ÷ Ni % bulk atomic composition ratio of 37 ÷ 12 ÷ 51 (and for binary Pt-Ni control systems of 47 ÷ 53). Fine topographical details as well as film thickness have been directly recorded using AFM microscopy. The composition of the outer layers as well as the interactions of the three metals present have been studied by XPS spectroscopy and a Pt ÷ Ru ÷ Ni % surface atomic composition ratio of 61 ÷ 12 ÷ 27 (and for binary Pt-Ni control systems of 85 ÷ 15) has been found, indicating the enrichment of the outer layers in Pt; a shift of the Pt binding energy peaks to higher values was only observed in the presence of Ru and points to an electronic effect of Ru on Pt. The surface electrochemistry of the thus prepared Pt-Ru(Ni)/GC and Pt(Ni)/GC electrodes in deaerated acid solutions (studied by cyclic voltammetry) proves the existence of a shell consisting exclusively of Pt-Ru or Pt. The activity of the Pt-Ru(Ni) deposits toward methanol oxidation (studied by slow potential sweep voltammetry) is higher from that of the Pt(Ni) deposit and of pure Pt; this enhancement is attributed both to the well-known Ru synergistic effect due to the presence of its oxides but also (based on the XPS findings) to a modification effect of Pt electronic properties.